Ceraeocercus Uvarov, a genus recorded in China for the first time (Orthoptera, Tettigoniidae; Tettigoniinae; Drymadusini) - Liu, Fei; Chobanov, Dragan Petrov; Chen, Liusheng; Liu, Chunxiang (Zootaxa, 2019)
Ceraeocercus Uvarov, 1910 of Tettigoniinae; Drymadusini is receded in China for the first time. Ceraeocercus fuscipennis fuscipennis Uvarov, 1910 is documented. Morphology and male calling songs are described and illustrations are provided.